THE URGENCE OF RESTORATIVE JUSTICE IN THE POLICE IN THE SETTLEMENT OF DOMESTIC VIOLENCE CASES (KDRT) - Saraya, Sitta Saraya (Universitas Duta Bangsa Surakarta, 2022)
Efforts to settle criminal cases in Indonesia do not always have to be resolved until the court is in the realm of the court, in this case the Court, until criminal sanctions are imposed. As in the widespread news related to Domestic Violence (KDRT) in Indonesia, this has become a serious concern for law enforcement officials, in this case the police. The police as law enforcement officers have the authority toterminate cases in accordance with applicable regulations, including the Regulation of the Indonesian National Police Number 8 of 2021 concerning the Handling of Crimes Based on Restorative Justice, as well as the Circular Letter of the Chief of Police Number SE/7/VII/2018 concerning Termination of Investigations. The author is interested in taking the title about the Urgency of Restorative Justice in the Police in Cases of Domestic Violence (KDRT), by formulating problems regarding the urgency of restorative justice in the Police in resolving cases of Domestic Violence (KDRT) and the weakness of the existence of restorative justice in resolving cases of violence. in the household (KDRT). The research method that the author uses is the sociological juridical method by conducting direct research in the field and also adding literature books, laws and regulations or relevant references. The purpose of this paper is to find out the urgency of restorative justice in the Police in resolving cases of domestic violence (KDRT) and to find out the weaknesses of the application of restorative justice.